LA CLASIFICACIÓN INTERNACIONAL DEL FUNCIONAMIENTO DE LA DISCAPACIDAD Y DE LA SALUD (CIF) 2001 - Ma. Teresa Jiménez Buñuales (Revista Española de Salud Pública, 2002)
The ap proach which had been being em plo yed to date fordea ling with and clas sif ying tho se as pects re la ted to healthand di sa bi lity have been re vi sed and up da ted thanks to theWorld Health Orga ni za tion (WHO) ha ving draf ted the Inter -na tio nal Clas si fi ca tion of Func tio ning, Di sa bi lity andHealth, which has now been ac cep ted 191 coun tries af ter re -vam ping the prior mo del and rea ching a con sen sus re gar dinga new in ter na tio nal mo del for des cri bing and mea su ringhealth and di sa bi lity.As back ground in for ma tion, it must be re ca lled that theClas si fi ca tion of Impair ments, Di sa bi li ties and Han di caps(CIDH) pre viously in ef fect was first pu blis hed by the WHO in1980. The pro cess of re vi sing this clas si fi ca tion has re sul ted insome chan ges of far-rea ching im portance. The chan ge in thename has been ai med at re flec ting the wish to re place the ne ga -ti ve pers pec ti ve of im pair ments, di sa bi li ties and han di caps fora more neu tral view of struc tu re and func tion, con si de ring thepo si ti ve pers pec ti ves of ac ti vi ties and of par ti ci pa tion. Anot hernew as pect has been that of in clu ding a sec tion re la ted to en vi -ron men tal fac tors in re cog ni tion of their im por tan ce, gi ven thatby in te rac ting with the health con di tion they may give rise to adi sa bi lity, or, at the op po si te end of the sca le, may res tore func -tio ning. The data avai la ble has ena bled the WHO make es ti ma -tes in clu ding that of some 500 mi llion years of life being lostan nually due to di sa bi li ties re la ted to health pro blems, whichto tals over one half of the years lost an nually due to pre ma tu redeaths.The main ob jective of this new clas si fi ca tion is that of pro -vi ding the con cep tual fra me work by means of uni fied, stan dar -di zed lan gua ge with a view to of the un derl ying cha llen ges, set -ting out a va lua ble ins tru ment of prac ti cal use in pu blic health.